Pengaruh Metode Pembelajaran Demonstrasi Terhadap Pemahaman Fikih Siswa MI Ulul Albaab - Siti Mubayanah Tawabie; Evi Herawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2025)
This study aims to determine the improvement of Fiqh learning outcomes of MI Ulul Albaab students by applying the demonstration learning method. This study used Classroom Action Research with a descriptive approach. The sources of information in this research include fiqh subject teachers and fourth-grade students of MI Ulul Albaab Madani Kelapa Dua Tangerang. Data were collected through observation, interviews, documentation, and test. Data analysis was carried out through three stages, namely data reduction, presentation and conclusion. The results showed that the application of the demonstration learning method had a positive impact on improving the learning outcomes of Fiqh students of MI Ulul Albaab. This improvement in learning outcomes was seen after the demonstration learning method was applied. In the early stages, 53.84% of students exceeded the standard. In the first and second cycles, it increased to 69.23% and 76.92%, and in the third phase, all students met the standard of completeness. It can be concluded that the application of the demonstration learning method can improve the learning outcomes of Fiqh students of MI Ulul Albaab.